2020
DOI: 10.1111/gcbb.12783
|View full text |Cite
|
Sign up to set email alerts
|

Does biochar improve all soil ecosystem services?

Abstract: Biochar is considered to sequester C and deliver other soil ecosystem services, but an overview that synthesizes the current knowledge of biochar implications on all essential soil ecosystem services is difficult to find in the ample biochar literature. Most previous research and review articles on this topic focused on a single ecosystem service and did not integrate all essential soil ecosystem services. This overview paper (1) synthesizes the impacts of biochar on water and wind erosion, C sequestration, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 77 publications
(201 reference statements)
0
34
0
Order By: Relevance
“…In general, biochar nowadays is considered for carbon sequestration and delivering different soil ecosystem services (Blanco-Canqui, 2021). Biochar is a porous carbonaceous solid material having a relatively high degree of aromatization and strong anti-decomposition ability (Blanco-Canqui, 2021;Bottezini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, biochar nowadays is considered for carbon sequestration and delivering different soil ecosystem services (Blanco-Canqui, 2021). Biochar is a porous carbonaceous solid material having a relatively high degree of aromatization and strong anti-decomposition ability (Blanco-Canqui, 2021;Bottezini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, biochar nowadays is considered for carbon sequestration and delivering different soil ecosystem services (Blanco-Canqui, 2021). Biochar is a porous carbonaceous solid material having a relatively high degree of aromatization and strong anti-decomposition ability (Blanco-Canqui, 2021;Bottezini et al, 2021). Biochar is generated by pyrolysis of plant biomass or animal wastes at elevated temperatures (350 °C to 1000 °C), under a limited supply of oxygen (Wu et al 2017;Ahmed et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite biochar can persist in the soil for thousands of years, and the impact of biochar on soil chemical, physical and biological properties may be a critical factor in the plant-soil system continuum, limited information on biochar aging is available (Hardy et al, 2019;Blanco-Canqui et al 2020;Wang et al 2020;Kalu et al 2021). Additionally, a limited number of long-term field studies examined the effect of biochar on crop productivity on fertile temperate agricultural soils, and most of this research was conducted under controlled laboratory or greenhouse conditions (Boersma et al 2017).…”
Section: Biochar As Soil Remediation Methodsmentioning
confidence: 99%
“…Although the effect of biochar addition to tropical and temperate soils has varying outcomes, it is suggested that the management approach between the two biomes should be different (Liu et al 2013). Blanco-Canqui (2020) synthesized which ecosystem services are or are not positively impacted by biochar amendment.…”
Section: Biochar As Soil Amendmentmentioning
confidence: 99%